Clean-AR: Using Augmented Reality for Reducing the Risk of Contamination from Airborne Disease Agents on Surfaces - Yu, Kevin; Ostler, Daniel; Fuchtmann, Jonas; Zapaishchykova, Anna; Berlet, Maximilian; Navab, Nassir; Feussner, Hubertus; Wilhelm, Dirk (Current Directions in Biomedical Engineering, 2021)
A core principle of modern health care is the compliance of hygienic and aseptic techniques in areas that are sensitive to contamination through bacteria, dust, aerosols, and fallout, primarily in operating theatres or around patients with contagious diseases. Keeping track of potentially contaminated surfaces in an environment is a major concern, especially when protecting from COVID-19. This work proposes a novel concept in using 3D sensing technology to track human movement within an indoor area and identifying high-risk contaminated surfaces in real-time. It combines recent Augmented Reality display technology, which allows keeping track of decontaminated surfaces during the cleaning process using an interactive visualization method. The proposed concept of Clean-AR is implemented in a clinical environment used for observation in COVID-19 scenarios. We discuss key challenges and outline further research direction in effectively reducing the risk of contamination using the proposed concept.
CRIS-Team Scopus Importer:2023-03-08
Keywords: augmented reality; head-mounted displays